Pemanfaatan Internet Sebagai Sumber Belajar Pendidikan Agama Islam Bagi Peserta Didik Di SMK PGRI Sooko Mojokerto - Alfiansyah, Mukhamad; Rozi, Syaikhu; Syarif, M. (STAI Denpasar Bali, 2023)
This study aims to describe the impact of utilizing the internet as a learning resource for Islamic Religious Education at SMK PGRI Sooko Mojokerto. The negative impact encountered in the use of the internet as a learning resource is that students become lazy to read books, more lazy to look in books because there is easy access on the internet, students can later misuse the internet outside the context of learning such as playing games to open other applications that have nothing to do with learning Islamic religious education. The positive impact is for teachers to be more practical to find teaching materials, provide material via the internet web and for students the positive impact makes it easier for them to find material and search for answers on the internet to add new insights and knowledge, because internet access and facilities in the form of wifi are adequate, it is hoped that this internet utilization can be used optimally and in these users the teacher must pay attention or accompany so that there will be no abuse of excessive internet use..